Principles of database and knowledge-base systems - Ullman, Jeffrey D (Computer Science Press, 1988)
Bibliography: pp.588 - 615; 10 Chapters: Databases, Object Bases, and Knowledge Bases; Data Models for Database Systems; Logic as a Data Model; Relational Query Languages; Object-Oriented Database Languages; Physical Data Organization; Design Theory for Relational Databases; Protecting the Database Against Misuse; Transaction Management; istributed Database Management